The Impact of Immigration: Why Do Studies Reach Such Different Results? - Christian Dustmann; Uta Schönberg; Jan Stuhler (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We classify the empirical literature on the wage impact of immigration into three groups, where studies in the first two estimate different relative effects, and the third the total effect of immigration on wages. We interpret the estimates obtained from the different approaches through the lens of the canonical model to demonstrate that they are not comparable. We then relax two key assumptions in this literature, allowing for inelastic and heterogeneous labor supply elasticities of natives and the downgrading of immigrants. We show that heterogeneous labor supply elasticities, if ignored, may complicate the interpretation of wage estimates, in particular of relative wage effects. Moreover, downgrading may lead to biased estimates in those approaches that estimate relative effects of immigration, but not in approaches that estimate total effects. We conclude that empirical models that estimate total effects not only answer important policy questions, but are also more robust to alternative assumptions than models that estimate relative effects.
Keywords: J21; J23; J24; J31; J61; 330; Immigration; impact; wage effects